Conceptualization of team situation awareness : attributes, measurement approach and underlying factors - Sulistyawati, Ketut (2008)
Situation awareness (SA) is about knowing and understanding what is going on, and projecting what is going to happen in the near future. Having good SA is vital for performance in a complex and dynamic environment. This has driven a great research interest on SA in the past two decades. The development is however limited to individual level. With the prevalence of teams in today’s organizational setting, an extension of SA concept to team level is needed. Despite its recognized importance, there has not been much research done in the area of team SA. Essentially, many questions are still unanswered. What do team members need to be aware of to be considered having a good team SA? What methods should be used to measure team SA? What are the underlying factors of team SA? What are the processes involved in the development and maintenance of team SA? This thesis aims to explore the fundamentals of SA in teams, specifically to define team SA and propose an integrated framework of team SA, which covers the underlying factors of team SA and approaches to measure the construct. This thesis includes an extensive review of SA and team literature to derive a comprehensive list of factors that would be relevant to team SA. Four laboratory-based studies were also conducted to provide empirical investigations of the construct. The first study involved military helicopter pilots performing navigational and combat tasks, the second and third studies involved gamers performing urban warfare simulation, and the fourth study involved military fighter pilots in simulated air combat scenarios. A definition of team SA proposed in this thesis is team members’ perception, comprehension, and future prediction of the system/task status relevant to their responsibilities, and of the team status, which is required for effective interaction in an interdependent team. It consists of two main aspects, namely awareness related to taskwork and awareness related to teamwork, which can be further broken down into the awareness of the situation necessary to perform own responsibilities, awareness of the elements needed to backup teammate’s responsibilities, awareness of own state of knowledge (meta-SA), and awareness of teammate’s workload and SA levels. An approach to assess team SA using a combination of methods is determined. The empirical investigations revealed that these aspects are non-overlapping; implying that team SA is a multifaceted concept and is best assessed by multiple methods. The application of multiple methods in conjunction would offer complementary roles, providing deeper insights of team SA, thus offering more confidence in drawing inferences regarding good and poor team SA through triangulation.